1969
DOI: 10.1002/aja.1001250406
|View full text |Cite
|
Sign up to set email alerts
|

Development of the lateral musculature in the teleost, Brachydanio rerio: A fine structural study

Abstract: The lateral musculature in the midbody region of the teleost, Brachydanio rerio, was examined by light and electron microscopy in the adult and six developmental stages. Two main divisions of the adult lateral musculature are described: (1) a superficial portion composed of small, dark fibers with high fat content and succinic dehydrogenase (SDH) activity; and (2) a deep portion composed principally of larger, pale, "deep fibers" showing little SDH activity and containing little fat. Some "intermediate fibers"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
1
2

Year Published

1970
1970
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 32 publications
4
107
1
2
Order By: Relevance
“…They suggested that as in the amniotes, such cells could originate from the dermomyotome, which have now been proved to also exist in fish in the form of the socalled external cell layer. An external cell origin of the new slow muscle fibres emerging from the lateral surface next to the lateral line nerve was supposed by several authors in different fish species as Danio rerio (Waterman, 1969), Clupea harengus (Linnaeus) (Johnston, 1993), Dicentrarchus labrax (Linnaeus) and Sparus aurata (Linnaeus) (Veggetti et al, 1990;López-Albors et al, 1998). As seen in other fish (Scapolo et al, 1988;Mascarello et al, 1995;Patruno et al, 1998), the appearance of those fibres coincided with the first attempts of the larvae at cruise swimming in search for food, and may be an important factor in larval survival at that age.…”
Section: Larvae Aged 0 (Hatching)-40 Daysmentioning
confidence: 96%
“…They suggested that as in the amniotes, such cells could originate from the dermomyotome, which have now been proved to also exist in fish in the form of the socalled external cell layer. An external cell origin of the new slow muscle fibres emerging from the lateral surface next to the lateral line nerve was supposed by several authors in different fish species as Danio rerio (Waterman, 1969), Clupea harengus (Linnaeus) (Johnston, 1993), Dicentrarchus labrax (Linnaeus) and Sparus aurata (Linnaeus) (Veggetti et al, 1990;López-Albors et al, 1998). As seen in other fish (Scapolo et al, 1988;Mascarello et al, 1995;Patruno et al, 1998), the appearance of those fibres coincided with the first attempts of the larvae at cruise swimming in search for food, and may be an important factor in larval survival at that age.…”
Section: Larvae Aged 0 (Hatching)-40 Daysmentioning
confidence: 96%
“…Located at the distal end of the common pathway and defining the nascent horizontal myoseptum, muscle pioneers are distinguishable from other somitic cells as the first to express muscle-specific characteristics (Waterman, 1969;van Raamsdonk et al, 1974;Myers et al, 1986;Felsenfeld et al, 1991;Hatta et al, 1991a) and assemble elements necessary for functional neuromuscular activity Hanneman and Westerfield, 1989;Westerfield, 1990, 1992). Zebrafish muscle pioneers fulfill criteria distinguishing guidepost cells in grasshoppers (for review, see Jellies, 1990;Palka et al, 1992) and intermediate targets in the rat CNS (Bovolenta and Dodd, 1990), mouse optic chiasm (Sretavan et al, 1995), and chick hindlimb plexus (Lance-Jones and Dias, 1991).…”
Section: Abstract: Acetylcholine Receptors; Neuromuscular Junctions;mentioning
confidence: 99%
“…Each layer is several muscle fibers thick. The red muscle is confined to a narrow region at the lateral edge of the segment, as described previously by Waterman (1969).…”
Section: Muscle Anatomymentioning
confidence: 99%